In vitro propagation of six selected sugarcane mutant clones through leaf explants. Issue 1 (October 2021) - Purnamaningsih, R; Sukmadjaja, D; Suhesti, S; Rahayu, S
Abstract: Six mutant clones of sugarcane with high productivity have been produced through tissue culture techniques combined with mutations using gamma-ray irradiation and Ethyl Methane Sulfonate. The six mutant clones have been tested for stability in the field. They are proven to have high productivity and yields, so that they are very potential to be developed as superior varieties. To support the planting material sufficiency of these clones, an efficient propagation method was needed. Media formulations with different physical properties and composition of growth regulators were tested to obtain high seedling propagation rates. The media formulation for callus induction was Murashige dan Skoog (MS) + 3 mg/l 2, 4-D + 3 g/l casein hydrolysate + 3% sucrose and for shoot regeneration was MS + 0, 5 mg/l BA + 0, 1 mg/l IBA + 100 mg/l PVP and 2% sucrose. Shoot proliferation was carried out on MS liquid (1, ½) + (0.3; 0.5 mg/l) BA + 0.1 mg/l IBA + 1 mg/l Kinetin + (0; 0.5 mg/l) GA3+ sucrose 2%. The results showed that callus induction, callus regeneration, and shoot proliferation of sugarcane mutant clones were influenced by the genotype and medium composition. The fastest callus induction was obtained from the MSP-4 clone (5.82 days), and the longest was MSB-7 (8.82 days). The largest callus diameter was obtained from MSB-6 clone on MS medium containing 1 mg/l BA, 100 mg/l PVP, and 2% sucrose. The highest number of shoots was obtained from the MSB-6 clone, while the least number of shoots conducted from the MSB-8 clone. The MSB-8 clones were more difficult to regenerate compared to the others. The best media formulation for shoot proliferation was ½ MS containing 0.5 mg/l BA, 1 mg/l Kinetin, and 0.1 mg/l IBA, while the best formulation for rooting was ½ MS.